Antioxidant pectin enriched fractions obtained from discarded carrots (Daucus carota L.) by ultrasound-enzyme assisted extraction. (15th August 2019) - Encalada, Alondra M. Idrovo; Pérez, Carolina D.; Flores, Silvia K.; Rossetti, Luciana; Fissore, Eliana N.; Rojas, Ana M.
Highlights: Misshapen carrots were upgraded to Ca 2+ gelling pectin enriched fractions (PEFs). PEFs were orange colored because of carotenes, lutein and α-tocopherol antioxidants. Sustainable ultrasound-pretreatment (US) and enzyme assisted extraction was used. US-hemicellulase led to the highest PEF yield (27.1%), extracting the whole pectins. US fell methylation degree and molecular weight, but gave the best yields and gelling. Abstract: Carrot residues were upgraded as pectin-enriched fractions (PEFs) useful for functional food formulation due to co-extracted antioxidants (α- and β-carotenes, lutein, α-tocopherol), and gelling effect. High power ultrasound (US)-enzyme assisted extraction was applied for efficiency and sustainability. Carrot powder (CP) in citrate-buffer (pH 5.20) was submitted to US-pretreatment (12.27 W/cm 2 : 20 kHz, 80% amplitude, 20 min) and a subsequent digestion (5 h-40 °C) without or with hemicellulase or cellulase. US-hemicellulase led to the highest PEF yield (27.1%), and extracted almost the whole pectin content of CP. US-pretreatment increased the extraction yield of all PEFs, but the existence of an additional positive effect of the following step depended on the enzyme used. PEFs contained 40–47% of UA with low DM (24–49.9%), and co-extracted antioxidants. US decreased the antioxidant contents, DM, and molecular weight, but allowed obtaining calcium crosslinked true gels, also with higher elastic modulus than non-US-extracted PEFs, being promising as food additives.